Geometry of non-holonomic complexes NGr (1, 4, 4) in a four-dimensional affine space - Navickis, Kazimieras (Lietuvos matematikos rinkinys, 2004)
In this article intrinsic normalizations of a non-holonomic complexes in affine space A4 is constructed in an invariant form.